KEMAMPUAN BERTUNAS STOOL PLANTS MERANTI TEMBAGA (Shorea leprosula Miq.) DARI BEBERAPA POPULASI DI KALIMANTAN - Mashudi Mashudi; Mudji Susanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
Vegetative propagation has an important role to produce high quality of seedling. Through vegetative propagation, the genetic potential of a mother tree will totally be inherited to the off-springs. Therefore, the success of stool plants preparation from selected mother tree is very important. The aim of study was to investigate the effect of populations and height of topping to sprouting ability of Meranti tembaga (Shorea leprosula Miq.) stool plants. This study was arranged in completely randomized block design with factorial. The two treatments used in the study were three populations (Muara Wahau, East Kalimantan; Kenangan, East Kalimantan and Ketapang, West Kalimantan) and four height of toppings (20 cm, 40 cm, 60 cm and 80 cm). The results of study showed that population were significantly different for the number of sprouts, length of sprouts, diameter of sprouts and number of nodus. While the height of topping were significantly different only for the number of sprouts. The best number of sprouts (6.82 buds), length of sprouts (18.41 cm), diameter of sprouts (2.14 mm) and number of nodus (7.10 nodus) was found at Muara Wahau population. While among the height of toppings, the best number of sprouts was found at 80 cm height (8,06 buds), followed by 60 cm (6,00 buds), 40 cm (5,08 buds) and 20 cm (3,86 buds). There were no significant differences on the interaction between population and height of topping for all measured characters.